EKSPERIMENTASI MODEL PROBLEM BASED LEARNING DAN DISCOVERY LEARNING PADA MATERI PERBANDINGAN DAN SKALA DITINJAU DARI SIKAP PESERTA TERHADAP MATEMATIKA DIDIK KELAS VII SMP KABUPATEN KLATEN TAHUN PELAJARAN 2013/2014 - Rahayu, Puji; Mardiyana, Mardiyana; Sari S, Dewi Retno (Jurnal Pembelajaran Matematika, 2015)
Abstrack: The aims of this research were to determine: (1) the better studentsâ achievement in learning by using Problem Based Learning (PBL), Discovery Learning (DL) or direct learning models (2) the better studentsâ achievement among the students who have positive, neutral or negative attitude (3) the better studentsâ achievement in each category attitude, in learning by using PBL, DL or direct learning models (4) the better studentsâ achievement in each learning model, among the students who have positive, neutral or negative attitude. This research used a quasi-experimental research with the population of seventh grade students of Junior High Schools in Klaten Regency which have implemented curriculum 2013 in the Academic Year 2013/2014. The sampling technique used stratified cluster random sampling and three schools selected namely SMPN 1 Delanggu, SMPN 1 Prambanan and SMPN 2 Wedi. Â Two-way variance analysis was used to test the hypothesis, followed by scheffeâ technique. Considering the result of analysis, the following conclusion could be drawn. (1) The studentsâ achievement who learnt by using DL was better than PBL and direct learning models. The studentsâ achievement who learnt by using PBL were similar to direct learning models. (2) The studentsâ achievement with positive attitude was better than neutral and negative attitude. The studentsâ achievement with neutral attitude was better than negative attitude. (3) In the positive and neutral attitude, the studentsâ achievement who learnt by using PBL, DL and direct learning models were similar. In the negative attitude, the studentsâ achievement who learnt by using DL model were better than PBL and direct learning models and the studentsâ achievement who learnt by using PBL and direct models were similar. (4) In learning by using PBL, the studentsâ achievement with positive attitude were better than negative one, the positive and neutral attitude ware similar and the neutral and negative attitude were similar too. In learning by using DL, the studentâs achievement with positive, neutral and negative attitude were similar. In learning by using direct learning, the studentsâ achievement with positive attitude were better than the negative one, the positive and neutral attitude were similar and the neutral and negative attitude were similar too.Keywords: Problem Based Learning, Discovery Learning, studentsâ Attitude, achievement of mathematics.